Association of vitamin D supplementation with respiratory tract infection in infants. Issue 3 (5th March 2020) - Hong, Miao; Xiong, Ting; Huang, Junmei; Wu, Yuanjue; Lin, Lixia; Zhang, Zhen; Huang, Li; Gao, Duan; Wang, Huanzhuo; Kang, Chun; Gao, Qin; Yang, Xuefeng; et al.
Abstract: Vitamin D deficiency has been reported to be associated with respiratory tract infection (RTI). However, evidence regarding the effects of vitamin D supplementation on susceptibility of infants to RTI is limited. In this prospective birth cohort study, we examined whether vitamin D supplementation reduced RTI risk in 2, 244 infants completing the follow‐up from birth to 6 months of age. The outcome endpoint was the first episode of paediatrician‐diagnosed RTI or 6 months of age when no RTI event occurred. Infants receiving vitamin D supplements at a daily dose of 400–600 IU from birth to the outcome endpoint were defined as vitamin D supplementation and divided into four groups according to the average frequency of supplementation: 0, 1–2, 3–4, and 5–7 days/week. We evaluated the relationship between vitamin D supplementation and time to the first episode of RTI with Kaplan–Meier plots. The associations of vitamin D supplementation with infant RTI, lower RTI (LRTI), and RTI‐related hospitalization were assessed using modified Poisson regression. The median time to first RTI episode was 60 days after birth (95% CI [60, 90]) for infants without supplementation and longer than 6 months of age for infants with supplementation ( p < .001). We observed inverse trends between supplementation frequency and risk of RTI, LRTI, and RTI‐related hospitalization ( p for trend < .001), with the risk ratios in the 5–7 days/week supplementation group of 0.46 (95% CI [0.41, 0.50]), 0.17 (95% CI [0.13, 0.24]), and 0.18 (95% CI [0.12, 0.27]), respectively. These associations were significant and consistent in a subgroup analysis stratified by infant feeding.